Detection of Copper by the ChemCam Instrument Along Curiosity's Traverse in Gale Crater, Mars: Elevated Abundances in Glen Torridon. Issue 3 (7th March 2023) - Goetz, Walter; Dehouck, Erwin; Gasda, Patrick J.; Johnson, Jeffrey R.; Meslin, Pierre‐Yves; Lanza, Nina L.; Wiens, Roger C.; Rapin, William; Frydenvang, Jens; Payré, Valerie; Gasnault, Olivier
Abstract: Laser‐induced breakdown spectroscopy, as utilized by the ChemCam instrument onboard the Curiosity rover, detected enhanced abundances of the element copper. Since landing in Gale crater (6 August 2012), 10 enhancements in copper abundance were observed during 3007 Martian days (sols) of rover operations and 24 km of driving (as of 20 January 2021). The most prominent ones were found in the Kimberley area on the crater floor (Aeolis Palus) and in Glen Torridon (GT) on the lower flanks of Aeolis Mons (Mt. Sharp). Enhancements in copper record the former existence of modestly acidic and oxidizing fluids, which were more oxidizing in Kimberley than in GT. Of the two main types of bedrock in the lowest part of GT, Mg‐rich "coherent" and K‐rich "rubbly" (named based on their outcrop expression), copper was detected only in coherent, not in rubbly bedrock. The difference between these two types of bedrock may be due to difference in provenance. Alternatively, based on a recently developed lacustrine‐groundwater mixing model, we suggest that rubbly bedrock was altered by modestly acidic, shallow‐subsurface lake water that leached out both copper and manganese, while coherent bedrock was affected by dominantly alkaline fluids which would be consistent with its mineralogical composition (including siderite) as returned by the CheMin instrument onboard the rover. Higher up in GT, ChemCam data indicated significant gradients in the copper concentration in coherent bedrock on a local scale of only a few meters, which suggests a different alteration style and possibly different types of diagenetic fluids. Plain Language Summary: Gale crater, Mars, about 152‐km in diameter and 3.6 Ga in age, has a central mound that is partly of sedimentary origin. To date (July 2022), the NASA rover Curiosity has been exploring the crater floor and the lower‐most 600 m (in elevation) of sediments of that mound. ChemCam, an instrument mounted on top of the remote‐sensing mast utilizing Laser‐Induced Breakdown Spectroscopy, has been measuring chemical composition and specifically copper abundances along the rover traverse. We identified 10 areas of copper enhancement along Curiosity's traverse. In the Kimberley formation on the crater floor, copper was identified in a manganese‐rich sandstone. Later on, some 350 m above Kimberley, high copper abundances were detected in magnesium‐rich mudstone and in iron‐rich sandstone in the Jura and Knockfarril Hill member, respectively. Following earlier work about copper in Gale crater (Payré et al., 2019, https://doi.org/10.1016/j.icarus.2018.12.015 ), we postulate a copper‐rich source region north of Gale crater and suggest that copper‐rich detrital material delivered to these areas in Gale crater. Taking into account the chemical and mineralogical composition of these types of bedrock, we conclude that copper was mobilized by later acidic and oxidizing fluids. Key Points: High copper abundances (200–400 ppm) are found in specific areas along the rover traverse In the Jura member in Glen Torridon (GT), copper is detected only in coherent bedrock, not in rubbly bedrock In the Knockfarril Hill member in GT, there is evidence for the redistribution of copper and iron by acidic, oxidizing fluids